(untitled) (Vietnam Journal of Community Medicine, 2026)
Objects: To assess the nutritional status of patients undergoing continuous ambulatory peritoneal dialysis at the Center for Nephrology - Urology and Dialysis, Bach Mai Hospital, in 2025. Methods: A cross-sectional descriptive study was conducted on 127 patients receiving continuous ambulatory peritoneal dialysis at the Center for Nephrology - Urology and Dialysis, Bach Mai Hospital. Results: According to the SGA scale, 74% of patients had no malnutrition, 22% had mid-moderate malnutrition, and 3.9% had severe malnutrition. Based on serum albumin levels, 38.6% of patients were malnourished (31.5% mid-moderate and 7.1% severe). The prevalence of anemia was high (74.8%), including 41.7% mild anemia, 29.1% moderate anemia, and 4% severe anemia. Serum urea, creatinine, and potassium levels were all above normal ranges, indicating that metabolic status and renal function considerably influenced the patients’ nutritional condition. Conclusion: Nutritional status remains a significant concern and is affected by multiple factors in patients undergoing continuous ambulatory peritoneal dialysis. Regular nutritional assessment, early identification of risk factors, and timely interventions play an important role in improving treatment effectiveness, quality of life, and patient prognosis.